LamJourney: Innovation of Learning Media Based on Historical Places in Lampung to Increase Historical Awareness - Dila Wedyanida Futrie; Rhoma Dwi Aria Yuliantri; Ardian Fahri (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
The development of technology in education encourages results in learning media for students. Historical places in Lampung can be used as a medium of historical learning for the younger generation by utilizing technological developments. This research uses the Research and Development (R&D) model with the ADDIE model. This study aims to develop learning media and see the influence of media use on increasing students' historical awareness of places in Lampung. Data collection techniques in this study used Observation, Interview, Documentation, and Literature Study Techniques. Testing the media's effectiveness was conducted in the Experiment and Control Class using Nonequivaalen Control Group Design at SMAIT Insan Mulia Boarding School. The results showed that the